(untitled) (Religious dialogue and cooperation, 2025)
This paper explores the concept of universal responsibility and global ethics as essential foundations for achieving lasting peace in the modern interconnected world. It emphasizes that genuine peace cannot be established through violence or coercion but through the cultivation of ethical values, moral awareness, and interreligious dialogue. The study argues that every human action has both personal and universal dimensions, demanding responsibility not only toward oneself but also toward humanity, nature, and future generations. Within this framework, dialogue emerges as a fundamental ethical and communicative method for understanding, cooperation, and peaceful coexistence among individuals, nations, and religions. Drawing on the ideas of thinkers such as Emil Brunner, the Dalai Lama, Emmanuel Levinas, and especially Hans Küng, the paper highlights Küng’s project Global Ethics as a crucial attempt to establish a shared moral framework based on humanism and dialogue. The work underscores the necessity of interreligious understanding and the development of a universal ethical paradigm grounded in justice, compassion, tolerance, and responsibility. The conclusion calls for an ethical revolution centered on humanism and global solidarity, affirming that universal ethics should guide humanity toward building a more humane, just, and harmonious world.